2019
DOI: 10.1590/fst.03618
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat Brazilian cooked sausage-Paio – with added oat fiber and inulin as a fat substitute: effect on the technological properties and sensory acceptance

Abstract: (Dnline) 2 Material and methods 2.1 Low-fat Paio processing Fresh beef (moisture 72.95%; fat 5.35%) and lean pork (moisture 71.06%; fat 9.53%) were provided by an industrial supplier (Frigorífico Dlhos D'água, Opuã, Brazil), while Frigorífico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
3
10
0
10
Order By: Relevance
“…The ash content exceeded the control sample by 1.9%. Similar results of the fat reduction were found by authors (Carvalho et al, 2019;Souza et al, 2019) with addition of hydrated wheat fiber (decreased by 32.6%) and oat fiber (a fat reduction around 60%). And all these findings are also in good agreement with the results of Serdaroglu (2006), Choi et al (2009), and Yang et al (2009).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The ash content exceeded the control sample by 1.9%. Similar results of the fat reduction were found by authors (Carvalho et al, 2019;Souza et al, 2019) with addition of hydrated wheat fiber (decreased by 32.6%) and oat fiber (a fat reduction around 60%). And all these findings are also in good agreement with the results of Serdaroglu (2006), Choi et al (2009), and Yang et al (2009).…”
Section: Resultssupporting
confidence: 87%
“…The technology of pâté with the addition of beans (10%) into turkey meat has been suggested by Martem'yanova et al (2017) and Serikova et al (2015) have promoted that rice grain or rice flour, used in foods, advanced their flavour and structure-forming properties. Using grains as additives in pâté preparation is the most advantageous way of formulating the preferred quality of formulations due to the impact of different nutrients making the end product more nutritious (Souza et al, 2019;Kim et al, 2016). Such additives can modify and most importantly improve various parameters such as texture, water-holding capacity, color and acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of two versions of oat fibre to light bologna and fat‐free frankfurters resulted in increase in hardness of the meat products compared to control 43 . Souza et al 39 . also observed increased cohesiveness and chewiness when oat fibre was added to a LF Brazilian cooked sausage – Paio .…”
Section: Resultsmentioning
confidence: 93%
“…The sausages processed without binder addition had the lowest WHC. Previous studies have shown enhanced water holding, hence cook yield when; oat fibre was used in reduced fat frankfurters, 38 LF Paio 39 and LF beef patties, 40 as well as when inner FB was used in beef patties 28,41 and when tapioca starch was used in reduced fat frankfurters 42 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the choice of components for fat substitution in meat emulsion products is of great importance. Prebiotic inulin is a functional food ingredient that has a future in this respect (Berizi et al, 2017;Mantzouridou et al, 2012;Shoaib et al, 2016;Souza et al, 2019). Regardless of the undoubtedly proven texturizing properties of inulin, there are different opinions in scientific literature concerning its use for the stabilization of the raw and thermally processed meat mass in the manufacture of meat products.…”
Section: Introductionmentioning
confidence: 99%